2017
DOI: 10.1097/cco.0000000000000411
|View full text |Cite
|
Sign up to set email alerts
|

Put away your microscopes: the ependymoma molecular era has begun

Abstract: Purpose of review To synthesize, integrate, and comment on recent research developments to our understanding of the molecular basis of ependymoma, and to place this in context with current treatment and research efforts. Recent findings Our recent understanding of the histologically defined molecular entity ependymoma has rapidly advanced through genomic, transcriptomic, and epigenomic profiling studies. Summary These advancements lay the groundwork for development of future ependymoma biomarkers, models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Recently, EPNs were classified according to the DNA methylation profile 6 , such classification showed to be increasingly dependent on molecular biology findings 29 . We highlight the WHO revised 2016 classification of CNS tumors 4 , which incorporates, for the first time, genetic information in addition to morphology for the classification of many tumor entities 30,31 .…”
Section: Methodsmentioning
confidence: 99%
“…Recently, EPNs were classified according to the DNA methylation profile 6 , such classification showed to be increasingly dependent on molecular biology findings 29 . We highlight the WHO revised 2016 classification of CNS tumors 4 , which incorporates, for the first time, genetic information in addition to morphology for the classification of many tumor entities 30,31 .…”
Section: Methodsmentioning
confidence: 99%
“…Supratentorial EPNs are divided into two distinct molecular subgroups: oncogenic mutually exclusive gene fusions involving either RELA or YAP1 [ 25 ]. Although Illumina DNA methylation provides an indirect measure of molecular subgroup associated with a particular fusion, fluorescence in situ hybridization (FISH) can be used to identify and verify samples harboring C11orf95-RELA fusion [ 15 ]. RNA-seq also provides an approach to identify C11orf95-RELA fusion as a discovery method to identify novel or less obvious fusion event.…”
Section: Molecular Subgroups Of Who Grade II and Iii Ependymomasmentioning
confidence: 99%
“…Interestingly, it has been reported that the level of resection does not significantly affect the outcome within the STEPN- RELA -positive subgroup in a retrospective analysis for patient samples collected over a long period of time over 20 years [ 25 ]. ST-EPN- YAP1 subgroup is associated with favorable clinical outcome [ 13 , 15 ]. Clinical trials with de-escalating therapy could be recommended for this subgroup.…”
Section: Treatment Decision In Molecular Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Many PFA ependymoma tumors have unremarkable whole-genome sequencing but exhibit epigenetic dysregulation, including H3K27 hypomethylation, and oncogenic gene expression (Bayliss et al, 2016;Mack et al, 2014;Pajtler et al, 2015). The lack of candidate genetic driver mutations has made modeling PFA ependymomas difficult, which has been compounded by the fact that patient-derived culture models have been particularly difficult to generate (Mack and Taylor, 2017). In a breakthrough study, Michealraj et al (2020) demonstrate that PFA ependymomas are dependent on metabolic changes driven by hypoxia, offering a compelling mechanism in which microenvironmental regulation of epigenetic state is an oncogenic driver in this disease.…”
mentioning
confidence: 99%